Mobilizing Bolivia's Displaced : Indigenous Politics and the Struggle over Land - Fabricant, Nicole (Book collections on Project MUSE., 2012)
The election of Evo Morales as Bolivia's president in 2005 made him his nation's first indigenous head of state, a watershed victory for social activists and Native peoples. El Movimiento Sin Tierra (MST), or the Landless Peasant Movement, played a significant role in bringing Morales to power. Following in the tradition of the well-known Brazilian Landless movement, Bolivia's MST activists seized unproductive land and built farming collectives as a means of resistance to large-scale export-oriented agriculture. In Mobilizing Bolivia's Displaced, Nicole Fabricant illustrates how landless peasa.